Improvement of Thyroid Function by Walnut Pulp Extract in Antidepressant-Treated Rats - Abd, Tiba Rami; M.J., Jiheel, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The current study was carried out to discover the role of alcoholic extract of walnut pulp in reducing the side effects of citalopram as antidepressant drugs. Crude extract of walnut pulp was extracted by using ethanol alcohol at a concentration of 70%. The experiment lasted for sixty days from seventh of April to sixth of June 2021. Twenty-eight adult male rats were divided into four equal groups, with age 2.5-3 months old, weighting 150-250g. All animals were drenched orally with gavage needle as the first group was given 0.5 ml of tap water daily and was considered a control group. The second and third groups were given respectively 10 and 20 mg/kg alcoholic extract of walnut pulp in addition to 6.0 mg/kg citalopram daily. While fourth group was treated with 6.0 mg/kg citalopram only oral doses were given. At zero time and after thirty and sixty days, blood samples were drawn by heart pincher after anesthesia with ketamine and xylazine and the thyroid functions were evaluated by measuring the concentration of serum thyroid-stimulating hormone (TSH), triiodothyronine (T3), and thyroxine (T4). Changes have been observed, such as loss of appetite, phenotypic changes such as pale-yellow skin color and hair loss. The results showed a decrease in thyroid-stimulating hormone in the second and third group who were dosed with walnut pulp alcoholic extract in addition to citalopram, and a decrease in the concentration of triiodothyronine and thyroxine in the second groups who dosed alcoholic extract of walnut pulp in addition to citalopram, and increase in serum triiodothyronine and thyroxine in the third groups who dosed 20mg/kg extract of walnut pulp in addition to citalopram. On the contrary, the results of the fourth group that was dosed with citalopram only, was recorded an increase in thyroid stimulating hormone and a decrease in both triiodothyronine and thyroxine. In conclusion, that citalopram has undesirable side effects on thyroid function. Alcoholic extract of walnut pulp has a role in reducing the side effects of citalopram, and the higher dose (mg/kg 20) showed a better effect than the lower dose.